Schooling Matters Opportunity to Learn in PISA 2012 - Schmidt, William H.. (OECD Education Working Papers, 2014)
Many international comparisons of education over the past 50 years have included some measure of students' opportunity to learn (OTL) in their schooling. Results have typically confirmed the common sense notion that a student's exposure in school to the assessed concepts, operationalized in some sort of time metric, is related to what the student has learned as measured by the assessment. What has not been demonstrated is a connection between the specifics of what students have encountered through schooling and their performance on any sort of applied knowledge assessment such as PISA. This paper explores this issue in 2012 PISA which, for the first time, included several OTL items on the student survey. OTL demonstrated a significant relationship with student performance on both the main paper-and-pencil literacy assessment as well as the optional computer-based assessment at all three levels - country, school and student. In every country at least one if not all three of the constructed OTL indices - exposure to word problems, formal mathematics topics, and applied mathematics problems - demonstrated a significant relationship to the overall PISA measure of mathematics literacy as well as the four sub areas of change and relationships, shapes and space, quantity, and uncertainty and data. Additionally, results indicated that variability in OTL was related to student performance having implications for equality of opportunity